تفعيل نية إنشاء مقاولة لدى الطلبة الجامعيين من خلال دار المقاولاتية – دراسة حالة: عينة من طلبة جامعة الوادي - علال, نبيل; عبد اللاوي, مفيد (جامعة الوادي - University of Eloued, 2022)
This study aimed to know the role of the entrepreneurial house at the university in activating the intention of establishing a business among university students and the extent of its impact on that. Data were collected for this through a questionnaire tool directed to a sample of (81) second-year master's students at the Faculty of Economics, Commercial and Management Sciences, El-Oued University. The data was also analyzed based on the spss.v26 program, and the results showed that there is an intention to establish a business for the students of the study sample, and the output also showed that the contracting house has a great role in spreading the entrepreneurial culture and thought among students, while it had a positive impact through what it does Among the activities in activating the intention of establishing a business for students.
Activating the intention of establishing a business for university students through the entrepreneurial House - Case study: A sample of El-Oued University students -
مقال
Keywords: نية مقاولاتية ; دار مقاولاتية ; مقاولاتية ; إنشاء مقاولة ; مقاول; entrepreneurial intention; entrepreneurial house; entrepreneurial; establishing a business; entrepreneur